Endocrine Disorders Associated with Medicinal Products: Approaches to Preclinical Safety Assessment - K. L. Kryshen; N. M. Faustova; M. N. Makarova; V. G. Makarov (Регуляторные исследования и экспертиза лекарственных средств, 2023)
The endocrine system coordinates almost all organs and other systems in vertebrates. In particular, it regulates such important biological functions as metabolism, development, reproduction, and behaviour. To date, a significant amount of information has accumulated on endocrine disorders associated with chemical compounds (endocrine disruptors) used in various fields of human activity. The aim of this study was to evaluate the possibility of preclinical risk assessment for the endocrine function disorders attributable to new medicinal products. Endocrine disruptors are associated with a wide range of adverse events, including developmental problems arising from functional abnormalities of the endocrine system. Endocrine disorders caused by endocrine-disrupting chemicals are characterised by a long latency period between exposure and manifestation of a dysfunction; a nonlinear dose–response relationship; and a linear correlation of damage severity to exposure timing and duration. The chemicals influence the endocrine system through multiple mechanisms, the main of which being the interaction with cellular receptors sensitive to certain hormones and the influence on gene expression, intracellular signalling, and hormone transport, etc. This paper discusses the possibility of using hormone levels as indicators of endocrine disruption and presents the literature and authors’ own data on normal levels of relevant hormones in the blood of animals. An analysis of animal blood hormone levels in preclinical programmes will provide an opportunity to evaluate potential iatrogenic risks.